2018
DOI: 10.1002/jtr.2193
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting casino revenue by incorporating Google trends

Abstract: This study investigates whether Google Trends has predictive power for improving casinorevenue forecasting. More specifically, the present study aims to (a) examine the value of using readily available Google Trends data to improve predictive accuracy in the forecasting of casino revenue and (b) compare domestic casinos and foreigner-only casinos given the significantly different spending patterns of such casinos' patrons. Accordingly, this research utilizes time-series analyses that incorporate Google Trend d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Li et al (2017), in turn, create a composite web search index for web data that improve forecast accuracy compared to traditional time-series models and a model with a web search index created by principal component analysis. The findings of Park et al (2016), Rivera (2016), Ö nder (2017b), Dergiades et al (2018), Kim andMalek (2018), andLiu et al (2018), who all analyze various aspects of Google Trends data, further corroborate the usefulness of Google Trends data in a tourism and hospitality forecasting context. However, Yang et al (2015) compare the predictive ability of Google Trends and Baidu for visitor numbers to Hainan, China, and find that the Baidu index is a better predictor for this destination due to Baidu being the most popular search engine in China.…”
supporting
confidence: 55%
“…Li et al (2017), in turn, create a composite web search index for web data that improve forecast accuracy compared to traditional time-series models and a model with a web search index created by principal component analysis. The findings of Park et al (2016), Rivera (2016), Ö nder (2017b), Dergiades et al (2018), Kim andMalek (2018), andLiu et al (2018), who all analyze various aspects of Google Trends data, further corroborate the usefulness of Google Trends data in a tourism and hospitality forecasting context. However, Yang et al (2015) compare the predictive ability of Google Trends and Baidu for visitor numbers to Hainan, China, and find that the Baidu index is a better predictor for this destination due to Baidu being the most popular search engine in China.…”
supporting
confidence: 55%
“…In South Korea, the gambling industry began modestly with horse racing and lottery ticket sales that were easily accessible to consumers (Kim and Malek ). Since the first foreigner‐only casino opened in 1967, other casinos have been permitted in tourist destinations such as Seoul, Jeju Island, and Busan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…exchange rates, oil prices, stock prices, interest rates, money supply, and exports). In investigating whether Google trends data has predictive power for improving casino revenues, Kim and Malek () found that such data indeed significantly improve forecasting for casino revenues. In other research, the location of casinos has been identified as an important source of competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations